Praktik Perjanjian Pinjam Nama (Nominee) di Kota Denpasar Bali Perspektif Hukum Positif dan Hukum Islam - Saleh, Hendri (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2020)
Abstract: This article examines the practice of nominee loan, which are commonplace among foreign citizens (WNA) in Denpasar, Bali. The practice of nominee loan agreement has provided countless number of foreigners with the land control in the city of Denpasar, Bali. The data in this study were collected through observation, in-depth interviews, and documentation. The data were analyzed using the agreement theory that applies in positive law and Islamic law. The study concludes that several factors have contributed to the rampant practices of nominee loan in Denpasar, Bali, namely: (a) the amount of payment/wages promised to the community members; (b) the presence of a notary who provides human resources for nominee loans; and (c) the less effective law enforcement against the parties who conduct or are involved in the nominee agreement. As seen from the perspective of Islamic law, this nominee agreement is not in line with the pillars and conditions for the formation of a contract based on Islamic contract law. In a positive legal perspective, the agreement is also determined as void due to a breach of the purpose of an agreement stated in Article 1320 of the Civil Code. In addition, nominee loan also violates the provisions of the UUPA (Basic Agrarian law) because the land is only reserved for Indonesian citizens.Abstrak: Artikel ini mengkaji praktik perjanjian pinjam nama (nominee) yang banyak dilakukan oleh Warga Negara Asing (WNA) di Kota Denpasar, Bali. Praktik perjanjian pinjam nama ini telah menjadikan banyak WNA mampu menguasai lahan yang ada di kota Denpasar Bali. Data-data dalam penelitian ini diperoleh melalui observasi, wawancara mendalam, dan dokumentasi. Analisis dilakukan dengan menggunakan teori perjanjian yang berlaku dalam hukum positif dan hukum Islam. Dari kajian yang dilakukan diperoleh simpulan bahwa ada beberapa faktor yang menjadi penyebab munculnya banyak praktik perjanjian pinjam nama di Kota Denpasar Bali, yakni: (a) besarnya bayaran/upah yang dijanjikan kepada warga masyarakat; (b) adanya oknum notaris yang menyediakan SDM untuk peminjaman nama; dan (c) lemahnya penegakan hukum terhadap para pihak yang melakukan atau terlibat dalam perjanjian pinjam nama. Ditinjau dari perspektif hukum Islam, perjanjian pinjam nama (nominee) ini tidak sesuai dengan rukun dan syarat terbentuknya akad dalam perjanjian syari’ah. Dalam perspektif hukum positif, perjanjian tersebut juga tidak sah (batal) karena adanya kausa yang tidak sesuai dengan tujuan perjanjian sebagaimana tertera dalam Pasal 1320 KUHPerdata. Selain itu, ia juga melanggar ketentuan UUPA karena tanah hanya diperuntukkan bagi WNI.